DEVELOPMENT OF A PREMIUM COLD MIX ASPHALT - Manar Hamzah Herez; Hassan Al Nageim; John Richardson; Sommerville Wright (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2023)
Cold mix asphalt produced using conventional emulsion and limestone filler has three main disadvantages, namely low early strength due to high amount of water within the mix, long curing time ranging from 2-24 months and high air voids content.